2022
DOI: 10.3390/ani12040518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myostatin Gene Mutation on Slaughtering Performance and Meat Quality in Marchigiana Bulls

Abstract: The myostatin gene also called Growth Differentiation Factor 8 gene (GDF8) is one of the most investigated loci that can be responsible for several quantitative and qualitative carcass and meat traits in double-muscled beef cattle. The objective of the study was to bring to light the effect of the myostatin polymorphism on slaughtering performance and meat quality in Marchigiana beef cattle. The experiment was carried out on 78 bulls reared according to the “cow-calf” extensive managing system. At the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…Although all of the animals bearing the TAATAA allele were of African (mainly North-African) origin, still, the geographically scattered distribution of this allele may suggest the presence of homozygous animals as rather uncommon. Similarly to our results, Ceccobelli et al, also in Marchigiana cattle, [ 54 ] did not found homozygote-mutated animals in the investigated dataset of 78 samples, and observed only a light superiority in the live weight reached by heterozygous bulls compared to wild-type bulls, although it was not significant. It is indeed known that the incredibly high muscularity typical of the double muscle phenotype generally occurs in association with a homozygous condition for the mutated allele at the myostatin locus.…”
Section: Resultssupporting
confidence: 91%
“…Although all of the animals bearing the TAATAA allele were of African (mainly North-African) origin, still, the geographically scattered distribution of this allele may suggest the presence of homozygous animals as rather uncommon. Similarly to our results, Ceccobelli et al, also in Marchigiana cattle, [ 54 ] did not found homozygote-mutated animals in the investigated dataset of 78 samples, and observed only a light superiority in the live weight reached by heterozygous bulls compared to wild-type bulls, although it was not significant. It is indeed known that the incredibly high muscularity typical of the double muscle phenotype generally occurs in association with a homozygous condition for the mutated allele at the myostatin locus.…”
Section: Resultssupporting
confidence: 91%
“…In this study, MSTN −/− pigs generated using TALEN genome editing had significantly inhibited activation of Smad, increased CSA of type IIb myofibers, and overgrowth of skeletal muscle, which was characterized by the 'double-muscle' phenotype. These findings are consistent with those of the previous studies performed in MSTN mutant mice and cattle Ceccobelli et al, 2022;Kambadur et al, 1997).…”
Section: Discussionsupporting
confidence: 94%
“…Myostatin (MSTN), a transforming growth factor β family member, is among the major regulators of skeletal muscle growth and development (Chen et al, 2021). Substantial muscle hypertrophy was observed in MSTN mutant animals and humans (McPherron et al, 1997; Ceccobelli et al, 2022; McPherron and Lee, 1997; Kambadur et al, 1997; Mosher et al, 2007; Kang et al, 2017; Schuelke et al, 2004). Recently various MSTN inhibitors, including monoclonal antibodies, have been tested in clinical trials to treat muscle disorders, such as sarcopenia and cancer-associated cachexia (Kim et al, 2021; Cho et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the polymorphism in SO cattle in this study might contribute to the differences in the composition of the MSTN gene, as indicated by the size of the DNA fragment. The mutation of MSTN in other cattle breeds is related to the double muscling trait, but mutation in SO cattle in this study might contribute to the growth and hypertrophy of muscles [ 3 , 29 , 38 ]. Further investigation is required to determine whether this mutation affects the phenotype of Ongole cattle.…”
Section: Discussionmentioning
confidence: 93%
“…The role of the MSTN gene in economic production has been identified in various breeds of beef cattle, such as Belgian blue [ 26 ], Nellore cattle [ 25 , 27 ], Piemontese young bulls [ 23 , 28 ], Russian cattle [ 2 ], Marchigiana bulls [ 3 ], and, Chinese yellow cattle [ 29 ]. The trait can be found in Australian beef cattle [ 30 ] and in some breeds of Indonesian beef cattle, such as the Peranakan Ongole (PO), the Belgian Blue × PO hybrid, and the PO × Pegolo Bali cattle [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%